Analysis Of Allocative Efficiency And Factors Affecting The Production Of Inorganic And Semi-Organic Rice Farming - Winahyu, Nastiti; Atika, Khofifa Nur; Maharani, Navita (Journal of Rural and Urban Community Studies, 2024)
The purpose of this research is to determine the allocative efficiency of the use of production inputs and factors that affect inorganic and semi-organic rice farming in Papar District, Kediri Regency. The methods used in this study are multiple linear regression analysis and allocative efficiency (price) analysis. The results of this study show that the factors that affect the production of inorganic rice fields are land area, chemical fertilizers, and pesticides, among the three factors that affect inorganic rice farming, the use of land area production inputs is not efficient so there needs to increase the land area. While the use of inputs in the production of chemical fertilizers and pesticides is known to be inefficient so there needs to be a reduction in the production input. Meanwhile, the results for factors that affect the production of semi-organic rice fields are land area, seeds, and manure. The use of land area production inputs is not yet efficient so it is necessary to add these inputs, while the use of seed and manure inputs is not efficient so there needs to be a reduction in the production input